Does the Simon Effect Interfere with the Synergy Between Perception and Action?. Issue 4 (August 2021) - Klostermann, André
Research suggests that – particularly – the execution of precision-demanding far-aiming tasks necessitates an optimal coupling between perception and action. In this regard, the duration of the last fixation before initiating movement – i.e., the Quiet Eye (QE) – has been functionally related to subsequent motor performance. In the current study, we investigated potential mechanisms of QE by applying the Simon paradigm – i.e., cognitive interferences evoked by stimulus-effect incompatibilities over response selection. To this end, we had participants throw balls as precisely as possible, either with their left or right hand (hands condition, HC) or at left or right targets (targets condition, TC), respectively. Via monaural auditory stimuli, participants received information about the hand side and the target side, respectively, either with compatible (i.e., congruent stimulus-effect side) or incompatible (i.e., incongruent stimulus-effect side) stimulus-effect mappings. Results showed that participants reacted slower and showed later first fixation onsets at the target in incompatible vs. compatible trials, thus, replicating and extending the classical Simon effect. Crucially, in the HC, there were earlier QE onsets and longer QE durations in incompatible (vs. compatible) trials, suggesting an inhibition of cognitive interferences over response selection to preserve motor performance. These findings are in line with attentional explanations of QE, suggesting optimized attentional control with efficient management of limited cognitive resources (optimal-attentional-control explanation) or with the inhibition of alternative response parametrization (inhibition explanation).